Examining Social Media Influencers (SMIs) Credibility on Followers’ Sharing Intention towards Food-Related Content among Malaysian Youth - Suhaimi , Muhamad Shukur; Ahmad Tajuddin, Siti Nor Amalina (Unisia, 2024)
Social media influencers (SMIs) have become increasingly influential in digital marketing, serving as key intermediaries between businesses and their target audiences. Despite their significant investments in time and resources to create engaging content, many SMIs struggle to maintain their follower base, often due to perceived deficiencies in source credibility. The link between SMIs’ credibility and followers’ sharing intention on food-related content among Malaysian youth is particularly under-examined. This study aims to bridge this gap by applying source credibility theory to examine how SMIs’ perceived credibility influences followers’ sharing intentions. The theory argues that how people think of communicators’ expertise and trustworthiness significantly influences individuals’ attitudes toward the source. Thus, by employing a quantitative approach through regression analysis, the study collected data via probability sampling with random respondent selection. The results indicate that perceived attractiveness is the best predictor of followers’ sharing intention on food-related content, overtaking both expertise and trustworthiness. These findings offer valuable insights for crafting more effective social media strategies that enhance engagement by focusing on the credibility aspects most valued by followers in the context of food content.